Synthesis of Admantane Substituted Spiro 1,2,4-Trioxanes Using Simple and Cheap Starting Material - KUMAR, LALIT; KAUSHIK, NIRANJAN; MALIK, ANUJ; KUMAR, PRADEEP (Asian Journal of Chemistry, 2010)
Spiro 1,2,4-trioxane are synthetic derivative of artemisinin (1,2,4- trioxane is supposed to be a pharmacophore of artemisinin) which is a well known antimalarial drug from leaves of Artemisia annua found in China. Spiro 1,2,4-trioxane substituted with admantane and its 4 different derivatives were synthesized using well standardized method. These compounds were purified by simple column chromatography and successfully analyzed using 1H NMR, IR and FAB-MS techniques.